Bio-psycho-socio-spiritual model of the holocaust trauma effects on survivors' health - Horáčková, Kateřina; Moravcová, Markéta; Ševčovičová, Andrea; Andraščíková, Ľudmila (My University, 2022)
This article introduces a bio-psycho-socio-spiritual model of the Holocaust impact on health. On the empirical level, the way to achieving the set goals leads through qualitative field research using the Interpretative Phenomenological Analysis approach. Three groups of respondents (Holocaust survivors,2nd generation of survivors and experts from helping professions who have experience with survivors care) were linked to ensure the validity of the stated conclusions. The main technique for data collection was a semi-structured interview. The data were analyzed using Atlas.ti software, following the IPA recommendations. The results refer to a wide range of physical impacts (e.g. osteoporosis, flat-foot, degenerative spine diseases, chronic pain, stomach and duodenal ulcer, chronic skin defects), mental impacts (e.g. PTSD, distrust, suspicion, vigilance, inferiority complex, annoyance in connection with the German language, specific attitude to food), social impacts (loss of property, marriages of convenience, need for education, inclination to care about weaker persons) and spiritual health impact (guilt, loss of faith in God, strengthening of Jewish identity, need to pass experience). Holocaust survivors are characterized by being interested in their health. Since the time of internment they have had their daily healing rituals, such as morning stretching exercises, yoga, cold baths, airing. Cleanliness of the body (especially the hands) and the environment are very important for all survivors. For most of them it is important to keep their mental health in good condition. That is the reason why they often attend various educational activities and if they are able to travel they do that. Research on the Holocaust Survivor Group represents the integration of resilience and vulnerability, desire for life, and the ability of a person to survive and live in extreme conditions. Using the example of this study examining the impact of trauma on health in all of its dimensions, it is possible to predict the future health problems of specific groups of migrants in connection with war conflicts and other life-threatening situations.
Bio-psycho-socio-spirituální model dopadů traumatu holokaustu na zdraví přeživších
Keywords: spiritual model; holocaust; trauma effect; spirituální model; holokaust; trauma